2020
DOI: 10.1063/5.0013345
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous interatomic bonding in chalcogenide crystals and implications on electronic, optical, and elastic properties

Abstract: Chalcogenide crystals are a unique class of materials very different from semiconductors or metallic alloys. They also have many practical applications, especially in relation to their optical properties. However, the fundamental understanding of their electronic structure and physical properties is rather scattered and incomplete. We present a detailed study using first-principles calculations on the electronic structure, interatomic bonding, and optical and mechanical properties for 32 chalcogenide crystals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 124 publications
0
16
0
Order By: Relevance
“…[ 15 ] This value is slightly higher than the calculated bulk modulus of Cu 2 Te K 0 = 22.9 GPa. [ 16 ] We observed no further phase transitions; at room temperature α‐Ag 18 Cu 3 Te 11 Cl 3 maintains the same structure up to ≈8 GPa.…”
Section: Resultsmentioning
confidence: 75%
“…[ 15 ] This value is slightly higher than the calculated bulk modulus of Cu 2 Te K 0 = 22.9 GPa. [ 16 ] We observed no further phase transitions; at room temperature α‐Ag 18 Cu 3 Te 11 Cl 3 maintains the same structure up to ≈8 GPa.…”
Section: Resultsmentioning
confidence: 75%
“…The γ is a measure of anharmonicity of lattice vibrations, which is usually determined by the chemical bonds and atomic masses of the constituent elements in a crystal . In our case, upon replacement of Cu by Ag, the weaker bonding of Ag–Te bonds compared to Cu–Te bonds and the heavier Ag atoms than Cu atoms tend to generate larger anharmonicity and thus lower κ L . In addition, it can be observed that κ L of AgInTe 2 is indeed much lower than that of CuInTe 2 , which can be ascribed to the stronger phonon scattering.…”
Section: Results and Discussionmentioning
confidence: 95%
“…The VASP optimized structures for all crystals were used as input to calculate the electronic structure, interatomic bonding, and optical properties using the OLCAO method with different choice of basis size for each atom in the database 45 . The use of localized atomic orbitals in the basis expansion in contrast to the plane-wave expansion is particularly effective for calculating the electronic structure and interatomic bonding for both crystalline 48 52 and non-crystalline materials 53 , 54 especially those with complex structures typical in the biomolecular systems 55 , 56 . In the OLCAO calculation, a sufficient number of k-points mesh were used for band structure and density of states (DOS) calculations based on the size of crystal.…”
Section: Methodsmentioning
confidence: 99%